2018
DOI: 10.3389/fpsyg.2018.00064
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Online and/or Face-to-Face Counseling among University Students in Malaysia

Abstract: Increasingly, online counseling is considered to be a cost-effective and highly accessible method of providing basic counseling and mental health services. To examine the potential of online delivery as a way of increasing overall usage of services, this study looked at students’ attitudes toward and likelihood of using both online and/or face-to-face counseling. A survey was conducted with 409 students from six universities in Malaysia participating. Approximately 35% of participants reported that they would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 27 publications
1
50
0
7
Order By: Relevance
“…The remaining three studies were conducted in Norway, 18 Spain, 19 and Malaysia. 20 In total, 22,024 participants took part in the selected studies, with individual sample sizes varying from 19 21 to 6,034 participants. 22 Response rate MONTAGNI ET AL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining three studies were conducted in Norway, 18 Spain, 19 and Malaysia. 20 In total, 22,024 participants took part in the selected studies, with individual sample sizes varying from 19 21 to 6,034 participants. 22 Response rate MONTAGNI ET AL.…”
Section: Resultsmentioning
confidence: 99%
“…27,29,40 On the contrary, some other studies reported that students presenting a mental health problem would prefer to interact with a person, whether that be a professional, a friend, or a family member. 20,21,26,32,35 Current usage and willingness to use e-mental health were, in fact, associated to perceived vulnerability 36 and the presence of a psychological problem. 17,18,22,34 In other words, the need for help with mental health issues appeared to be a strong predictor of students' intention to use e-mental health for support seeking.…”
Section: Purposes Of Mental Health-related Digital Usementioning
confidence: 99%
“…OVC is as effective when compared with F2F for providing cognitive behavior therapy to those experiencing panic disorder with agoraphobia (Bouchard et al, ), bulimia nervosa (Mitchell et al, ), and various other psychological disorders (Day & Schneider, ). Although OC has been successfully used to treat specific psychological concerns, attitudes toward this modality have been identified as less favorable when compared with F2F (Lewis, Coursol, Bremer, & Komarenko, ; Rochlen, Beretvas, & Zack, ; Wong, Bonn, Tam, & Wong, ). When investigating how these attitudes and stigma are related, researchers have found that stigma is negatively related to F2F attitudes (Vogel et al, ).…”
mentioning
confidence: 99%
“…Por ejemplo, Richards (2009) ha encontrado que los estudiantes que han tomado servicios de consejería psicológica virtual en el Trinity College de Dublin, Irlanda han mostrado altos niveles de satisfacción con el mismo y Wong, Bonn, Tam & Wong (2018) también han encontrado lo mismo en estudiantes de la Universidad de Malasia. Esto demuestra que la modalidad de consejería psicológica virtual, puede tener un impacto positivo en los estudiantes si se fomenta una cultura de la interacción virtual (Carmona & Rodríguez, 2017;Vásquez & Arango, 2012) en las instituciones de educación superior y si se definen buenos programas de capacitación 5 (Pipoly, 2013;Ekong, 2006) y atención en consejería psicológica virtual (Poh, et al, 2013).…”
Section: Conclusionesunclassified